2011
DOI: 10.1186/ar3350
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab in ankylosing spondylitis: alone or in combination with methotrexate? A pharmacokinetic comparative study

Abstract: IntroductionMethotrexate (MTX) has been shown to modify infliximab pharmacokinetics in rheumatoid arthritis. However, its combination with infliximab in the treatment of ankylosing spondylitis (AS) is not recommended. The objective of this study was to examine the influence of MTX on infliximab exposure in patients with AS.MethodsPatients with AS patients who had predominantly axial symptoms were randomised to receive infliximab alone (infusions of 5 mg/kg at weeks 0, 2, 6, 12 and 18) or infliximab combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 19 publications
1
33
0
1
Order By: Relevance
“…Because the effect of csDMARD is dependent on both the disease and individual TNFi agent, differences in these variables among different cohorts may explain observed discrepancies. Along with other studies 5 , we found no protective effect of MTX co-medication in AS; this finding is supported by smaller studies 17,18 . On the contrary, investigators from the Antirheumatic Therapies In Sweden registry reported a positive effect of MTX 10 .…”
Section: Rheumatologysupporting
confidence: 88%
“…Because the effect of csDMARD is dependent on both the disease and individual TNFi agent, differences in these variables among different cohorts may explain observed discrepancies. Along with other studies 5 , we found no protective effect of MTX co-medication in AS; this finding is supported by smaller studies 17,18 . On the contrary, investigators from the Antirheumatic Therapies In Sweden registry reported a positive effect of MTX 10 .…”
Section: Rheumatologysupporting
confidence: 88%
“…There is no evidence that combining MTX with TNFi improves efficacy, but it may affect persistence in peripheral SpA. In AS, addition of MTX to IFX did not affect outcomes, infusion numbers, TNFi switching, or dosing 111,112,113,114,115 . In PsA, RCT demonstrated clinical and radiographic efficacy of several TNFi regardless of concomitant MTX 102,106,116,117,118 .…”
Section: Tumor Necrosis Factor Inhibitors (Tnfi)mentioning
confidence: 90%
“…However, three clinical trials comparing infliximab alone to a combination of infliximab and methotrexate found no superiority in terms of efficacy and allergic adverse events for the combination therapy. [34][35][36] Thus, no evidence current ly supports the use of such a regimen.…”
Section: Immunogenicity Efficacy and Switchingmentioning
confidence: 96%